In Vitro Evaluation of Antimicrobial, Antioxidant, and Cytotoxic Effects of Sumac (Rhus coriaria L.)/Rose Water Mouthwash: In vitro evaluation of Sumac/Rosewater mouthwash - Torshabi, Maryam; Shahbazi, Razieh; Nikoosokhan, Maryam (Journal of Dental School, 2024)
Objectives Mouthwashes are one of the most effective non-mechanical methods for removing bacteria from the mouth. This study aimed to assess the cytocompatibility, antimicrobial effects (compared to chlorhexidine mouthwash), and antioxidant activity of an experimental herbal mouthwash made from sumac (Rhus coriaria L.) and rose water. Methods The sensitivity of Streptococcus mutans, S. sanguinis, Staphylococcus aureus, Candida albicans, and Aggregatibacter actinomycetemcomitans to the experimental mouthwash was estimated by measuring the diameter of the inhibition zones. Additionally, the minimum inhibitory concentrations (MICs) were determined using the redox dye resazurin, as well as the minimum bactericidal/fungicidal concentrations (MBCs/MFCs) using the standard spot inoculation method. Cytotoxicity was evaluated using the methyl thiazolyl tetrazolium (MTT) assay, while antioxidant activity was assessed using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay. Results The MIC and MBC of the sumac mouthwash for the bacteria under study (except S. mutans) ranged from 0.13 to 16.65 mg/mL. For the yeast C. albicans, the MIC and MFC of the sumac mouthwash were determined to be 0.52 mg/mL. Furthermore, the sumac mouthwash showed no cytotoxicity and demonstrated significant antioxidant effects at various concentrations. Conclusion Sumac/rose water mouthwash, which is a safe, natural, biocompatible, and antioxidant product, may serve as a viable alternative to chemical antibacterial mouthwashes like chlorhexidine. This is particularly true when it is used in conjunction with regular oral hygiene practices over extended time periods.